An Analysis of Compliment Used by the Teacher in the Classroom at SMA Negeri 5 Lubuklinggau - Cellya Ayu Febriani; Dewi Syafitri; Ayu Oktaviani (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The objective of this research was to analysis of compliment used by teacher in the classroom at SMA Negeri 5 Lubuklinggau. The method applied in this research was descriptive qualitative. The subject in this research was an English teacher at SMA 5 Lubuklinggau. The data was analyzed by describing the types of compliments used observation sheet, interview and documentation (field note and voice record). In analyzing the data, the research identified two types of compliments verbal and nonverbal compliments used by the teacher by using Usman (2017) theory. Based on the result of data analysis, the researcher found five kinds of verbal compliments, namely good (31 data), very good (19 data), well done (2 data), good job (20 data), excellent (3 data). And also the researcher found five kinds of nonverbal compliments namely applause and thumbs (5 data), gesture head movement (43 data), contact touching (5 data), gesture face expression (28 data), standing near to students (5 data). In conclusion, by giving a compliment the students’ mood to participate in the learning process can increase so that it will create a good atmosphere for both teachers and students.